The use of in vitro culture in dianthus propagation - Marković Marija; Grbić Mihailo; Đukić Matilda (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2013)
Today, in vitro culture is of the great importance in both scientific investigation of under-researched plant species and plant production. In this paper, a review of development and methods of in vitro culture is presented. The main principles are given and the most commonly used methods are described. Special attention was paid to the propagation of Dianthus spp. Tissue culture of commercially important taxa is described in detail, and the review of propagation of other decorative Dianthus spp. that can be used as ornamental plants is also given. [Projekat Ministarstva nauke Republike Srbije, br. 43007: Istraživanje klimatskih promena na životnu sredinu - praćenje uticaja, adaptacija i ublažavanje]